Mitochondrial and nuclear diversity of colonies of varying origins: contrasting patterns inferred from the intergenic tRNAleu-cox2 region and immune SNPs. Issue 3 (5th May 2022) - Henriques, Dora; Lopes, Ana R.; Chejanovsky, Nor; Dalmon, Anne; Higes, Mariano; Jabal-Uriel, Clara; Le Conte, Yves; Reyes-Carreño, Maritza; Soroker, Victoria; Martín-Hernández, Raquel; Pinto, M. Alice
Abstract: In this study, we gathered sequence data from the tRNA leu -cox2 intergenic mitochondrial (mtDNA) region concurrently with single nucleotide polymorphism (SNP) data from 91 loci of nuclear DNA (ncDNA). The data was obtained from 156 colonies sampled in six apiaries from four countries. The full dataset was analysed and discussed for genetic patterns with a focus on cytonuclear diversity and admixture levels.